An Architecture for Redundant Multicast Transmission Supporting Adaptive QoS - Christos Bouras; Apostolos Gkamas; Kostas Stamos; A Karaliotas (7th International WORKSHOP ON MULTIMEDIA SYSTEMS, Capri, Italy, 2001)
In this paper we describe the architecture and the implementation of an application that was developed for the transmission of multimedia data, using the multicast mechanism, over the Internet. There are two major issues that have to be considered when designing and implementing such a service, the fairness and the adaptation schemes. The fairness problem results from the fact that receivers with different capabilities have to be served. In our application we use a mechanism that categorizes the receivers into a number of groups according to each receiver’s capabilities and (the mechanism) serves each group of users with a different multicast stream. With the term “capabilities” we do not only mean the processing power of the client, but also the capacity and the condition of the network path towards that client. Because of today’s Internet heterogeneity and the lack of Quality of Service (QoS) support, the sender cannot assume that the receivers will permanently be able to handle a specific bit rate. We have therefore implemented an additional mechanism for the intra-stream bit rate adaptation.